Mendorong Reformasi Parlemen Melalui Kekuatan Civil Society Di Indonesia - Pratama, Sandy; Hidayat, Arief; Aisyah, Putri (Jurusan Ilmu Politik Universitas Bangka Belitung, 2019)
This paper aims to provide a critical review of the repositioning of the institutionalization of opposition in parliament and strengthening the function of control of parliament itself by civil society. The dynamics of the new post-order political system urges the creation of a system of checks and balances that is capable of accommodating the complicated issue of public policy governance in presidential systems with this multi-party parliament. This paper is a descriptive analytical study. Data sources were obtained from references about political parties and elections and power relations between political forces. This paper takes the setting of a parliamentary loophole that requires the presence of a control body on the balancing function of executive power as a consequence of the manifestation of authority that tends to be dilemmatic. The author concludes that the network of civil society can be the dominant alternative to carrying out a supervisory role on legislative performance in parliament. When executives are constitutionally unable to adequately compensate for the function of parliamentary oversight, repositioning of civil society organizations that are considered as a complete and ideal representation of the interests of many people is the best choice to reduce the strengthening of collusive democracy. Synchronization of regulations, good intentions of political parties, the role of control of civil society, and the synergy of the perspective on the consequences of multiparty systems that grow into the basis of more advanced democratization.